Performance of clinical features as predictor of streptococcal tonsillitis and macrolides resistance - Elnaim Bushra Ahmed; Elsir Ali Abu Groun; Babiker Saad Almugadam; Nadir Abuzeid (Biomedical and Biotechnology Research Journal, 2022)
Background: Streptococcus pyogenes is a significant pathogen that causes various types of human diseases which range from mild to fatal illness. This work was designed to assess the value of symptoms in the prediction of disease and macrolides resistance. Methods: We conducted a cross-sectional hospital-based study during 2020–2021 in Kosti Teaching Hospital (Kosti city, Sudan) to evaluate the link between symptoms with Group A Streptococcus (GAS) infection. Streptococcal tonsillitis was diagnosed by throat swabs culture, and macrolides resistance was detected by phenotypic and genotypic methods. Results: There was no significant variation in the mean of reported symptoms between gender and residence. Macrolides resistance and resistance genes had no significant effect on symptoms. On correlation analysis, age and education level were negatively correlated with symptoms score. Conclusions: The study highlights the link between symptoms with GAS tonsillitis and suggests the requirement for more care in children.